Influence of 1-Methylcyclopropene on the biochemical response and ripening of ‘solo' papayas - Ohashi, Thaís Luri; Foukaraki, Sofia; Souza Corrêa, Daniel; Ferreira, Marcos David; Terry, Leon A. (Sociedade Brasileira de Fruticultura, 2016)
The market demand for tropical fruits has been growing steadily over the past two decades and global papaya production has grown significantly over the last few years. This sector, however, suffers greatly from postharvest losses due to reduced quantity and quality of fruits between harvest and consumption. The use of ethylene inhibitors after harvest could improve the final quality of the fruit to satisfy the consumer and also minimize waste. The physiological and biochemical responses of ‘Solo’ papayas treated with the ethylene inhibitor 1-methylcyclopropene (1-MCP) to extend storage shelf life and maintain quality during long-term storage are deeply discussed in this study. Papaya fruits arrived at Cranfield University (CU) and received a 24 h 1-MCP, being stored at 20 ºC for 10 days. The ethylene inhibitor 1-MCP application significantly delayed ‘Solo’ papaya ripeness on fruit storage by reducing respiration rate and ethylene production. There was a delay from 7 days in fruit firmness loss and the retention of green peel colour was increased. Inhibition of ethylene perception by 1-MCP did not prevent the accumulation of sugars and the mean values were similar and higher than those found for control fruits, which are possibly due to the lower reaction speed, leading to a higher accumulation.
Keywords: Carica papaya L.; fruit quality; fruit waste; 1-MCP; tropical fruits